Ophthalmic implications of biological threat agents according to the chemical, biological, radiological, nuclear, and explosives framework - Curran, Emma H.; Devine, Max D.; Hartley, Caleb D.; Huang, Ye; Conrady, Christopher D.; Debiec, Matthew R.; Justin, Grant A.; Thomas, Joanne; Yeh, Steven (Frontiers in Medicine, 2024)
As technology continues to evolve, the possibility for a wide range of dangers to people, organizations, and countries escalate globally. The United States federal government classifies types of threats with the capability of inflicting mass casualties and societal disruption as Chemical, Biological, Radiological, Nuclear, and Energetics/Explosives (CBRNE). Such incidents encompass accidental and intentional events ranging from weapons of mass destruction and bioterrorism to fires or spills involving hazardous or radiologic material. All of these have the capacity to inflict death or severe physical, neurological, and/or sensorial disabilities if injuries are not diagnosed and treated in a timely manner. Ophthalmic injury can provide important insight into understanding and treating patients impacted by CBRNE agents; however, improper ophthalmic management can result in suboptimal patient outcomes. This review specifically addresses the biological agents the Center for Disease Control and Prevention (CDC) deems to have the greatest capacity for bioterrorism. CBRNE biological agents, encompassing pathogens and organic toxins, are further subdivided into categories A, B, and C according to their national security threat level. In our compendium of these biological agents, we address their respective CDC category, systemic and ophthalmic manifestations, route of transmission and personal protective equipment considerations as well as pertinent vaccination and treatment guidelines.